Ultra-rapid CO gas detection by a gas sensor based on flame-spray-made Pt/ZnO nanoparticles - Tamaekong N. (2014)
ZnO nanoparticles doped with 0.2-2 at.%Pt were successfully produced in a single step by flame spray pyrolysis (FSP) technique using zinc naphthenate and platinum (II) acetylacetonate dissolved in xylene. The particle properties were analyzed by XRD, BET and TEM. Depending on FSP conditions, ZnO nanoparticles and nanorods were observed. The crystallite sizes of ZnO spheroidal particles were found to be ranging from 5 to 20 nm, while ZnO nanorods were seen to be 5-20 nm in width and 20-40 nm in length. ZnO sensing films were prepared using Al 2O3 substrate interdigitated with Au electrodes by spin-coating technique. The gas sensing properties toward carbon monoxide (CO) was studied at the operating temperatures ranging from 200 to 350° C. It was found that the 0.2 at.%Pt/ZnO sensing film showed the highest sensitivity and the fastest response time at 350°C. © (2010) Trans Tech Publications.